A review of the South American metalmark genus Alesa Doubleday, 1847 (Lepidoptera: Riodinidae: Eurybiini) with the description of two new species - Santos, Wildio Ikaro Da Graça; Dolibaina, Diego Rodrigo; Dias, Fernando Maia Silva; Mielke, Olaf Hermann Hendrik; Casagrande, Mirna Martins (Zootaxa, 2023)
The taxonomy of the South American metalmark butterflies of the genus Alesa Doubleday, 1847 is reviewed. A new taxonomic arrangement for Alesa is supported after the analysis of about 600 specimens, including the recognition of two new species, described herein, A. juliae sp. nov. and A. mariae sp. nov.. Alesa negra Röber, 1931, so far recognized as a junior subjective synonym of A. telephae (Boisduval, 1836), is here recognized as a valid species (stat. rev.) and A. amethystina Gallard & Fernandez, 2015 as a junior subjective synonym (syn. nov.) of A. negra, and A. fournierae Lathy, 1958 is recognized as a junior subjective synonym (syn. nov.) of A. amesis (Cramer, 1777). Neotypes are designated for Papilio amesis Cramer, 1777, Erycina prema Godart, [1824] and Mimocastinia egeria Biedermann, 1936. Lectotypes are designated for Erycina priolas Godart, [1824], Eurybia telephae Boisduval, 1836, A. smaragdifera Westwood, 1851, A. lipara Bates, 1868, A. hemiurga Bates, 1868, A. thelydrias Bates, 1868, and Mimocastnia rothschildi Seitz, 1913. Three previously established species groups are here supported by morphological characters including the following species, “prema group”: A. prema, A. esmeralda Salazar & Constantino, 2007, A. beneluzi Gallard & Fernandez, 2015, A. rothschildi and A. juliae sp. nov.; “telephae group”: A. telephae, A. humilis Brévignon, 2015, A. negra stat. rev. and A. suzana Ahrenholz & Hall, 2010; and “amesis group”: A. amesis, A. mariae sp. nov., A. lipara Bates, 1867, A. hemiurga Bates, 1867 and A. thelydrias Bates, 1867. Adults and their genitalia are illustrated for all species available to examination. The main diagnostic characters used to distinguish the species belonging to the “amesis group” are illustrated, and pictures of adults images in situ and distribution maps are provided. Additionally, all species are diagnosed and discussed based on their morphology.